Autonomy movements in Mizoram - Prasad, R. N. (Ram Narayan), 1941-; Seminar on Autonomy Movements in Mizoram Since Independence (1991 : Aijal, India) (New Delhi : Vikas Pub. House, 1994)
Substantially the outcome of papers/articles presented at the Seminar on Autonomy Movements in Mizoram Since Independence, held in Aijal in 1991.
Includes bibliographical references and index.
Keywords: Mizoram (India) -- History -- Autonomy and independence movements -- Congresses